46‐4: Novel OLED Low Frame Frequency Driving Method with Minimized Flicker. Issue 1 (25th September 2020) - Li, Jieliang; Yuan, Yong; Ding, Yuan; Huang, Wanming; Ke, Zhoulin; Zhang, Yuheng; He, Shui; Lai, Qingjun; Xu, Yuping
Abstract : We analyzed flicker of OLED and minimized it under low frame frequency with changing the emit pulse width and frequency. We also report a novel low frame frequency driving method for minimzing image flicker under ‐50dB although the average brightness is 450nit with attenuation ‐30nit during emission.